2020
DOI: 10.1038/s41388-020-01424-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts downregulate type I interferon receptor to stimulate intratumoral stromagenesis

Abstract: Activation of cancer-associated fibroblasts (CAFs) and ensuing desmoplasia play an important role in the growth and progression of solid tumors. Here we demonstrate that, within colon and pancreatic ductal adenocarcinoma tumors, efficient stromagenesis relies on downregulation of the IFNAR1 chain of type I interferon (IFN1) receptor. Expression of the fibroblast activation protein (FAP) and accumulation of the extracellular matrix (ECM) was notably impaired in tumors grown in the Ifnar1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…106 107 A recent study by Cho et al showed that IFNAR1 deficient cancer-associated fibroblasts play a significant role in stromagenesis and contribute to rapid tumor growth. 108 Conversely, when IFNAR1 is intact, conventional therapies can induce IFN-β and lead to induction of HLA-I expression. 109 110 For example, Wan et al observed HLA-I upregulation in breast cancer cell lines following topotecan treatment due to elevated levels of IFN-β signaling.…”
Section: Microenvironmental Regulation Of Hla Expressionmentioning
confidence: 99%
“…106 107 A recent study by Cho et al showed that IFNAR1 deficient cancer-associated fibroblasts play a significant role in stromagenesis and contribute to rapid tumor growth. 108 Conversely, when IFNAR1 is intact, conventional therapies can induce IFN-β and lead to induction of HLA-I expression. 109 110 For example, Wan et al observed HLA-I upregulation in breast cancer cell lines following topotecan treatment due to elevated levels of IFN-β signaling.…”
Section: Microenvironmental Regulation Of Hla Expressionmentioning
confidence: 99%
“…IFN1 biological activity is mediated by a heterodimeric receptor complex composed of IFNAR1 and IFNAR2 chains [ 83 ]. Proteolytic loss of IFNAR1 in the nonimmune tumor microenvironment promotes a stable activation of CAFs and enhances tumor growth, whereas stabilization of the receptor attenuates the pro-tumorigenic phenotype of CAFs [ 84 ]. Mice deficient in IFNAR1 exhibit enhanced expression of Smad7 in fibroblasts, and knockdown of Smad7 in such cells alleviates deficient ECM production in response to TGF-β1 [ 84 ].…”
Section: Smad7 In Colon Cancermentioning
confidence: 99%
“…Proteolytic loss of IFNAR1 in the nonimmune tumor microenvironment promotes a stable activation of CAFs and enhances tumor growth, whereas stabilization of the receptor attenuates the pro-tumorigenic phenotype of CAFs [ 84 ]. Mice deficient in IFNAR1 exhibit enhanced expression of Smad7 in fibroblasts, and knockdown of Smad7 in such cells alleviates deficient ECM production in response to TGF-β1 [ 84 ]. These data raise the possibility that Smad7 is one of the mediators of the IFN1-driven suppression of stromagenesis.…”
Section: Smad7 In Colon Cancermentioning
confidence: 99%
“…Our findings showed that Sac/Val markedly suppressed the activation of the TGF-β1/Smad3 signaling pathway during the progression of the high-salt diet-induced cardiac fibrosis. The expression of Smad7, which is a feedback inhibitor of TGF-β, was increased by treatment with Sac/Val ( Cho et al, 2020 ), suggesting that this pathway was probably involved in the cardioprotective effects of Sac/Val.…”
Section: Discussionmentioning
confidence: 99%